On contradictions in conversation - Jarosław, Jabłonka (Folia Philosophica, 2000)
In the present paper, the author refers to the principle of contradiction formulated by Jan Lukasiewicz, according to whom this principle „is the only defence against errors and lies”. The author presents a certain method of analysing conversations which takes into account the intuitions that provided the foundations for the said principle. In the situation where the sender of a message uses two syntactically contradictory statements, it is not suggested that the receiver should try to surmise the sender’s intentions and infer from this a judgement. The suggested approach is contrasted with Grice’s theory of conversational implicatures, which, by means of making use of conversational maxims, admits semantically contradictory utterances. The main claims the author makes in his paper are the following: 1. For the interlocutors to observe the principle of contradiction if the conversation is focused on transmitting truthful information is one of the essential criteria of the sensibility of such a conversation, and, because the suggested approach does not take into account the interlocutors’ intentions, any mistake that has been made can be exposed. 2. Any analysis of the way the colloquial language is used should take into account the subjectivity of the action of expressing judgements through a sentence and of inferring a judgement from a sentence. 3. One of the adequate tools in a formal and logical analysis of a colloquial conversation is provided by the versions of the dialogic logic formulated and developed by Ch. Hamblin, and J. Mackenzie with the help of which we can study such problems which the standard logic cannot resolve in a satisfactory way.